Chrysin and its emerging role in cancer drug resistance. (5th July 2015) - Kasala, Eshvendar Reddy; Bodduluru, Lakshmi Narendra; Barua, Chandana C.; Gogoi, Ranadeep
Abstract: This letter illustrates the significant chemosensitizing effects of chrysin to resistance cancer cells and refers to the article on "Combination of chrysin and cisplatin promotes the apoptosis of Hep G2 cells by up-regulating p53" by Li et al., published in your journal recently. Recent studies have demonstrated that chrysin is able to sensitize or kill cancer cells which are resistant to chemotherapeutic drugs such as cisplatin, doxorubicin and adriamycin. Owing to its potential anti-cancer effects and devoid of toxicity to non-transformed cells, further research is required to completely explore its chemosensitizing effects in other cancers and also assess and evaluate its safety, before going for possible human application.